Development of Comic Media to Improve Problem Solving Abilities and Interest in Learning Mathematics Subjects of Elementary School: English - Firmansyah, Firmansyah; Irnandi, Irfan; Siregar, Nahrun Najib; Simamora, Ebeneser Wacner; Indriyani (Jurnal Elementaria Edukasia, 2024)
This research aims to develop Class IV Mathematics Comic Media with Fraction Material that is valid, practical and effective to improve elementary school students' problem solving abilities and interest in learning mathematics subjects. This research method is development research or Research and Development (R & D). The procedure used is to simplify the Borg & Gall development model (in Sugiyono, 2015: 298-331) which consists of 10 steps, in this research it will be limited to the seventh step. The population in this study is the population in this study are students at SD Negeri 02 Amban. The research sample chosen was class IV students for the 2023/2024 academic year. The sample in this study was divided into two, namely class IV A students as the experimental class and class IV B students as the control class. Data collection techniques used in this research include questionnaires, interviews, validator assessment sheets, and problem solving ability tests. The data analysis techniques used in this research consist of three, namely validity, practicality and effectiveness data analysis. The research instruments consisting of learning implementation plans, student worksheets, comic media, problem solving ability tests, and learning interest questionnaires that have been developed are in the very good category based on the assessments of the three validators. Practicality obtained a positive response from students of 88.6%, which is in the very practical category. Students' problem solving abilities are better than the problem solving abilities of Control class students. The average problem solving ability of Control Class students is 60.31, while the average problem solving ability of experimental class students is 72.50. There is an influence of interest in learning on students' problem solving abilities.